An application of finite element technique or solving B.P.L equations - RAMANATHAN, N; NATARAJAN, R (MAUSAM, 1986)
In order to solve the differential equations of meteorological parameters finite difference method is used and fed to computers. In this paper finite element technique is used for the present result the solution of atmospheric planetary boundary layer (PBL) equations. The results obtained by this solution, such a technique are comparable in accuracy with those obtained by finite difference method.